2007
DOI: 10.1259/bjr/31771954
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the effects of lead shielding for fetal dose reduction in CT pulmonary angiography

Abstract: This work aims to determine whether lead shielding can be used to decrease the radiation dose to the fetus during CT scans for the diagnosis of pulmonary embolism during early stage pregnancy. An anthropomorphic phantom was modified to contain a 15 cc ionization chamber at the site of the uterus to enable fetal dose to be measured. The effects of a range of scan parameters, positioning of lead and thicknesses of lead were investigated. Fetal dose was lower with lower values of kV(p) and mAs. An increasing thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…The most radiosensitive organ fully in the protected area, according to ICRP 103 [23], is the colon, which has a tissue weighting factor of 0.12; the measured dose reduction to the colon was 33.2%. The reduction in the dose to the uterus with the new shield in place was 35.4% and was 42.1% with the conventional aprons; this agrees well with the value of 39.7% found by Kennedy et al [13] using a Siemens Sensation 16 scanner.…”
Section: Dose Savings Per Phantom Sectionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most radiosensitive organ fully in the protected area, according to ICRP 103 [23], is the colon, which has a tissue weighting factor of 0.12; the measured dose reduction to the colon was 33.2%. The reduction in the dose to the uterus with the new shield in place was 35.4% and was 42.1% with the conventional aprons; this agrees well with the value of 39.7% found by Kennedy et al [13] using a Siemens Sensation 16 scanner.…”
Section: Dose Savings Per Phantom Sectionsupporting
confidence: 89%
“…In recent years a number of papers have shown that abdominal shielding yields foetal dose reductions of approximately 35% in both early and late stage pregnancy when patients undergo chest CT [13][14][15]. Despite this evidence, out-of-plane shielding has not been used regularly in CT scanning even though the use of such shielding has no effect on the quality of the images produced.…”
mentioning
confidence: 99%
“…The use of a lead apron/shield to cover the abdomen during CTPA has been shown to moderately reduce the leakage and scattered radiation to the uterus from the CT collimators. 33 We found that maternal breast dose is generally higher for CTPA than for VQ, but organ-based tube current modulation has been shown to reduce this. 35 Further opportunities to reduce CTPA radiation doses include the use of statistical and model-based iterative reconstruction techniques, 36 reducing the tube voltage, as we have already performed from 120 to 100 kVp, 37 increasing the pitch to above 1 and decreasing the scan volume.…”
Section: Dosimetrymentioning
confidence: 74%
“…The relevant quantity for planning the exposure of patients and risk-benefit assessments is the equivalent dose or the absorbed dose to irradiated tissues. 33 Readers may wish to refer to a general discussion on the typical errors associated with the application of effective dose to medical exposures, 34 which reports a relative uncertainty of about 640% for a reference patient and still higher for this study, where we have attempted to report the dose to individuals. Similar limitations apply to dose calculations for radiopharmaceuticals.…”
Section: Dosimetrymentioning
confidence: 99%
“…25,32 The radiation risk for the foetus is less than with a VQ scan. 23 Exposure of the foetus can be reduced by 43 using a lead apron with a thickness of 0.7 mm that covers the patient. A lesser thickness can be used over the back of the patient, maximising the distance between the edge of the scan and the foetus.…”
Section: Diagnosismentioning
confidence: 99%